Effect of (3-aminopropyl) trimethoxysilane and (3-aminopropyl) triethoxysilane on mechanical, thermal and morphological properties of kenaf fiber reinforced poly(lactic acid)/poly(butylene adipate-co-trerephthalate) blends - Mohd Sis, Anith Liyana (2012)
The effect of (3-aminopropyl)trimethoxysilane (APTMS) and (3-aminopropyl)triethoxysilane (APTES) on composite based poly(lactic acid)(PLA)/poly(butylene adipate-co-terephthalate) (PBAT) blends reinforced kenaf fiber has been prepared by using melt blending technique. Composites were blended for 15 minutes at 170°C until the blends became homogenized. Composites with the ratio of 90:10 PLA/PBAT blend and ratio of 90:10 PLA/PBAT blend with kenaf fiber have been characterized and the results revealed that the mechanical properties have decreased sharply with the addition of kenaf fiber. However, addition of APTMS and APTES into PLA/PBAT blend reinforced kenaf fiber demonstrated the improvement of its mechanical properties up to 42.46%,62.71% and 22.00% for tensile strength (52.27 MPa), flexural strength (64.27 MPa) and impact strength (39.79 J/m) respectively. Morphological observation through scanning electron microscopy (SEM) reveals improved interaction and interfacial adhesion between PLA/PBAT blend and kenaf fiber with addition of APTMS. The fiber was well distributed and pulling into PLA/PBAT blend evenly. Dynamic mechanical analysis (DMA) result shows a decreased in storage modulus (E’) for PLA/PBAT blend reinforced fiber, but addition of 2% APTMS, the E’ increased. Conversely, the relative damping properties decreased. Thermogravimetric analysis (TGA) thermogram showed improved thermal properties in the presence of APTMS. Differential scaning calorimetry (DSC) analysis was used to evaluate the crystallization of PLA/PBAT/Kenaf composites. Addition of APTMS, cause the width of crystallization peaks to reduce indicating of an increase in crystallization rate. The composite also shows the inward shifting of melting peaks of polymer constituent indicating improved compatibility between PLA/PBAT and Kenaf. Beside APTMS, the effect of adding APTES as coupling agent has been investigated. However, it produced contradictory result as addition of 2% APTES does not show any significant changes either in mechanical or thermal properties. The tensile strength increase only by 1.69%, nevertheless, the flexural strength and impact strength decrease to the tune of 0.05% and 8.39% respectively. These results was supported by SEM micrographs where some of kenaf fiber still pull out after addition of APTES. Moreover, based on DMA graph, composite with APTES added displays lower E’ compared to the composite modified by APTMS. TGA thermogram reveals composite modified by APTES displays 81.32% of degradation, which was 8.48% lower than polymer degradation of composite modified by APTMS. Whereas, differential thermogravimetric (DTG) curve demonstrated there was no significant effect between composite modified by APTMS and APTES since composite/APTMS demonstrated thermal stability at 308.30°C. Furthermore, the degradation test on the composite by soil buried in laboratory and at landfill area has been carried out in order to ensure the composite is an environmental friendly materials. Therefore, within nine months, result indicates that presence of kenaf fiber into PLA/PBAT matrix was induced the degradability rate. The weight loss of PLA/PBAT/Kenaf was increase up to 7.1% (soil in laboratory) and 5.48% (soil at landfill area) compared to the PLA/PBAT blend which displays weight loss only by 0.24% and 0.78% respectively. Modification by silane coupling agent, PLA/PBAT/Kenaf/APTMS and PLA/PBAT/Kenaf/APTES shows 5.66% and 6.12% of weight loss respectively for sample that has been soil buried in laboratory. Whereas, demonstrated 6.22% (PLA/PBAT/Kenaf/APTMS) and 6.58% (PLA/PBAT/Kenaf/APTES) of weight loss for sample buried in soil at landfill area.